The Influence of the Use of Learning Management Systems and On-the-Job Training on Improving Teachers' Professional Competence in In-Depth Learning - Rahmaniar Rahmaniar; Hartini Hartini; Muhammad Fahreza W (EDUJAVARE: International Journal of Educational Research, 2026)
The learning approach in the world of education has an important role in efforts to realize students who have skills that can meet the challenges of 21st century education. This study aims to determine the effect of the use of Learning Management System (LMS) and On the Job Training (OJT) on the professional competence of teachers in Bulukumba Regency, both partially and simultaneously. This study uses a quantitative approach with a survey method. The research data was obtained through the distribution of questionnaires to 18 respondents who were teachers in Bulukumba Regency. The data analysis technique used is multiple linear regression analysis which includes partial tests (t-test), simultaneous tests (F tests), and determination coefficients with the help of statistical data processing programs. The results showed that partially the use of LMS had a significant effect on teachers' professional competence, while the OJT variable also had a significant effect on teachers' professional competence. Simultaneously, the use of LMS and the implementation of OJT have a significant effect on teachers' professional competence. The Adjusted R Square value of 0.365 indicates that 36.5% of the variation in teachers' professional competence can be explained by these two variables, while the rest is influenced by other factors outside the research model. Thus, the use of the LMS and the implementation of OJT have a positive and significant influence on improving the professional competence of teachers in Bulukumba Regency.